Available Sources of Food in Indonesia (for the improvement of the nutritional status of children) - Lie Goan-Hong; Oey Kam-Nio; Dradjat D. Prawiranegara; Tudit Herlina; Geertruida Sihombing; Idrus Jus'at (Paediatrica Indonesiana, 1976)
Ultimately, improvement of the nutritional status of children, in especially the preschool children, can only be achieved if the daily food intake is sufficient.This will ensure in the first instance the adequate provision -of energy, and secondly, the available protein in the diet will then be efficiently utilized. Sufficient intake of food can and must be realized through the combined use of inexpensive locally available foods from the food groups: Cereals, Legumes and Fish, Fat, Vegetables and Fruits, according to the existing menu-pattern "4 Sehat - 5 Sempurna" (4 means healthy- 5 is excellent). The diet therefore must not consist of rice alone. The role of fat in the diet must be stressed. The meal pattern of preschool children must be at least l times a day, preferably more. Depending on the available budget and the creative imagination of the mother, a variety of inexpensive but palatable dishes can be prepared at home which will stimulate the food intake.